Smart Manufacturing Technology Adoption for Improving Productivity: A Systematic Literature Review - Satria; Matondang, Nazaruddin; Ishak, Aulia (Jurnal Sistem Teknik Industri, 2023)
This paper is to present a review of the Smart manufacturing application as Industry 4.0, specifically on the conceptual approaches to define it. Two conceptual approaches to the application of the concept of smart manufacturing are distinguished. The method using the previous articles of scientific journals from 2017-2022 (thirty-two international paper) were selected based on previous works, with the scope to investigate and analyze in-depth the extent to which literature used to discuss results in the selected studies of applying the Smart Manufacturing Technology in manufacture enterprises. The results of the previous studies are discussed and investigated in a table format.